A low-loss variable-doped trench-insulated gate bipolar transistor with reduced on-state voltage. (28th May 2021) - Vaidya, Mahesh; Naugarhiya, Alok; Verma, Shrish; Prasad Mishra, Guru
Abstract: The performance of a superjunction trench-insulated gate bipolar transistor with variable vertical doping in the epitaxial region along with variation in the collector layer is investigated. The concept of vertical variation transfers the avalanche multiplication point from the epitaxial edges to the middle of the pillar. The proposed device offers increased effective doping in the drift region, which reduces the on-state voltage ( V on ) without any degradation in the breakdown voltage. Furthermore, the horizontal doping variation in the collector layer supports the phenomenon in two ways: the left section of the collector layer reduces V on whereas the right portion enables an efficient discharging path, which allows improved switching performance. In addition to this, a reduction in the gate to collector charge ( Q GC ) is observed because of the presence of a lightly doped n-region below the gate terminal. A two-dimensional numerical simulation revealed that the proposed device offers a 15.30% reduction in Q GC compared with the conventional device. The structural modification offers a 40% reduction in turn-off time, resulting in a reduction in turn-off energy loss ( E off ).